Proposals for Institutional Changes in the Management of the Euro Area: Euro Area Treasury, European Minister of Economy and Finance, European Monetary Fund - Zieliński, Marek (Polish Review of International and European Law, 2022)
European Union member states which have been outside the euro area are obliged to join it as soon as they are able to fulfil the necessary convergence criteria. As a result of the financial crisis of 2008 and the consequences following it, euro area member states have adopted additional rules regulating its functioning which make the accession to the euro area even more difficult for those concerned. In addition to this some member states and EU institutions have proposed other measures which have as their aim to establish new institutions and organs involved with the management of the euro area. The present paper aims at describing three of those institutions (the Euro Area Treasury, European Minister for Economy and Finance, European Monetary Fund) and to evaluate the potential impact of their entry into force on those member states who (as Poland and Czechia) have been outside the euro area. In order to achieve this aim the author analyses proposed changes in more details and provides an assessment.